Association of total sedentary behaviour and television viewing with risk of overweight/obesity, type 2 diabetes and hypertension: A dose–response meta‐analysis. Issue 1 (1st October 2019) - Guo, Chunmei; Zhou, Qionggui; Zhang, Dongdong; Qin, Pei; Li, Quanman; Tian, Gang; Liu, Dechen; Chen, Xu; Liu, Leilei; Liu, Feiyan; Cheng, Cheng; Qie, Ranran; et al.
Abstract: Aims: To explore the quantitative dose–response association of total sedentary behaviour and television viewing with overweight/obesity, type 2 diabetes and hypertension in a meta‐analysis. Materials and methods: We searched three databases to identify English‐language reports that assessed the association of total sedentary behaviour or television viewing with the aforementioned health outcomes. Restricted cubic splines were used to evaluate possible linear or non‐linear associations of total sedentary behaviour and television viewing with these health outcomes. Results: We included 48 articles (58 studies) with a total of 1 071 967 participants in the meta‐analysis; 21 (six cohort and 15 cross‐sectional) studies examined the association of total sedentary behaviour with overweight/obesity, 23 (13 cohort and 10 cross‐sectional) studies examined the association with type 2 diabetes and 14 (one cohort and 13 cross‐sectional) studies examined the association with hypertension. We found linear associations between total sedentary behaviour and type 2 diabetes ( P non‐linearity = 0.190) and hypertension ( P non‐linearity = 0.225) and a non‐linear association between total sedentary behaviour and overweight/obesity ( P non‐linearity = 0.003). For each 1‐h/d increase in total sedentary behaviour, the risk increased by 5% for type 2 diabetes and 4% for hypertension. We also found linear associations between television viewing and type 2 diabetes ( P non‐linearity = 0.948) and hypertension ( P non‐linearity = 0.679) and a non‐linear association for overweight/obesity ( P non‐linearity = 0.007). For each 1‐h/d increase in television viewing, the risk increased by 8% for type 2 diabetes and 6% for hypertension. Conclusions: High levels of total sedentary behaviour and television viewing were associated with overweight/obesity, type 2 diabetes and hypertension.